Effects of the addition of hormone in maturation medium for in vitro production ofembryo (IVP). - Situmorang, Polmer; Triwulanningsih, Endang; Lubis, Adriana; Hidayati, Nurhasanah; Sugiarti, Tatit (Indonesian Animal Sciences Society, 1998)
A study on the effects of hormone FSH, hCG and estrogen in maturation medium on embryo production (IVP) was conducted. Ovaries of dairy cows were obtained from slaughtered house and oocytes were collected by aspiration and slicing. Oocytes were matured in TCM-199 media containing one of each hormonal treatments : 10 ug/ml FSH, 2 IU hCG, 1 ug/ml estrogen, 10 ug/ml FSH + 2 IU hCG, 10 ug/ml FSH + 1 ug/ml estrogen, and 10 ug/ml FSH + 2 IU hCG + 1 ug/ml estrogen for 24 hours. Fertilization was conducted in thyroid albumin lactate pyruvate (TALP) media containing 10 ug/ml heparin for 18-24 hours and co-cultured in synthetic oviduct fluid (Sof-media) using C02 incubator at 38oC. Every 48 hours the embryos were moved into fresh Sofmedia and embryo evaluation was done on day 7using a microscope . From a total of 293 oocytes studied resulted 60.4% of zygotes which develop to 9.4% young embryos ( cell numbers <16), 45.3% morulae and 5,7% blastocysts. Hormones used singly did not significantly affect the production of embryo . The highest mean percentages of fertilization wasobtained in FSH (73.3%) and the lowest in estrogen (59.6%), but the mean percentage of blastocyst was higher in estrogen . The mean percentages of young embryos, morulae and blastocysts were 4.8, 66.1, 2.4 ; 18 .8, 41 .6, 6.6 and 3 .3, 46.6, 10 .0 for FSH, hCG and estrogen, respectively . Using a combination of FSH with hCG and estrogen did not significantly increase the production of embryo . The mean percentages of fertilization, young embryo, morulae and blastocysts were 55.2, 9.3, 43.4 and 2.6 ; 51 .7, 4.8, 35.8 and 11 .1 and 56 .0, 12 .3, 42.3 and 1 .4 for FSH+hCG, FSH+estrogen and FSH+hCG+estrogen respectively . Â Keywords: Embryo, fertilization, hormone, in vitro